Analysis of the Effect of Foreign Direct Investment, International Tourism Receipts, and Exchange Rate on GDP in ASEAN-4 - Choirunnisa, Hanifah; Sishadiyati, Sishadiyati (PT. Riset Press International, 2024)
The dynamically evolving global economy creates great challenges for policy makers. Southeast Asia as a regional economic driver seeks to strengthen strategic measures through ASEAN. However, economic fluctuations become a problem as the economy grows in the region. The purpose of this study is to analyze the effect of Foreign Direct Investment, International Tourism Receipts, and Exchange Rate on Economic Growth in four ASEAN countries (Indonesia, Malaysia, Thailand, and the Philippines). The methodology used is panel data regression with a time span from 2013 to 2022, focusing on four ASEAN countries. The independent variables in this study are foreign direct investment, international tourism revenue, and exchange rate, while the dependent variable is gross domestic product. The results showed that the variables of international tourism receipts and exchange rates had a significant effect on economic growth, while the variable of foreign direct investment had no effect on economic growth.